The Role of Neutrophil-Lymphocyte Ratio (NLR) as a Predictor of Successful Thrombolysis in Patients with STEMI at RSUP Dr. Sardjito - Rahadiyani, IDA Swasty; Dinarti, Lucia Kris; Hartopo, Anggoro Budi (Faculty of Medicine Universitas Gadjah Mada, 2023)
Background. Coronary atherosclerosis is a major cause of ST-elevation acute myocardial infarction (STEMI). Many factors influence the pathophysiology of atherosclerosis formation, and one of the most important is inflammation. Neutrophils have an important role in the progression and instability of atherosclerotic plaques that lead to acute coronary syndromes, while lymphopenia is caused by an increase in endogenous cortisol that occurs during acute stress in acute coronary syndromes. The neutrophil-lymphocyte ratio (NLR) is a combination of inflammatory markers, integrating the two roles of leukocyte subtypes with their respective pathways into one predictor factor that can be applied to the outcome stratification of patients with STEMI undergoing thrombolytic therapy.Objectives. To identify the role of NLR as a predictor of successful thrombolysis in patients with STEMI and knowing the NLR cut-off point that can act as a predictor of successful thrombolysis in patients with STEMI.Method. This study was a retrospective cohort study. The research subjects were patients who were first diagnosed with STEMI in the ER/ICCU Dr. Sardjito Hospital and who met the inclusion and exclusion criteria, from January 1, 2016, to November 30, 2020. The independent variable in this study was the NLR at admission. The dependent variable in this study was the success of thrombolysis. Characteristic data in this study are presented in the form of categorical data. Bivariate statistical analysis with Chi-Square test. The prognostic value for success of thrombolysis was analyzed using the Receiver Operating Characteristic curve to determine the NLR limit value, followed by calculating the Relative Risk (RR). Variables having p<0.25 were continued in multivariate analysis.Result. A total of 162 subjects met the inclusion and exclusion criteria. Overall, the success of thrombolysis was 81.5%. NLR values are in the range of 6 to 13 with a median value of 6.38. ROC NLR analysis on the success of thrombolysis obtained a cut-off of 10.16 fL. From the bivariate analysis for all possible predictors, 6 predictors had logistical significance (p<0.25) namely NLR, gender, age, BMI, onset, and Killip. From multivariate analysis, statistically significant independent predictors of thrombolysis success were NLR (p=0.007, OR 3.44), onset (p=0.003, OR 4.13), and Killip (p=0.009, OR 6.76).Conclusion. A low NLR can be used as a predictor of successful thrombolysis in STEMI patients at RSUP Dr. Sardjito, with 3.44 times higher compared to the high NLR.